Weaponizing nature: The geopolitical ecology of the US Navy's biofuel program. (September 2017) - Bigger, Patrick; Neimark, Benjamin D.
Abstract: The United States military is treating climate change as a crucial factor in its preparation for future conflicts. This concern manifests not only in strategic planning and forward-looking documents, but also in building infrastructural capacity and material provision. Yet, the impetus to 'green' the military goes beyond the deployment of existing technologies. We examine several facets of the military's role as an environmental actor, particularly through its promotion of the US Navy's 'Great Green Fleet' (GGF), which actively supports the development of advanced biofuels by subsidizing their development and facilitating wider marketization. The GGF promises to reduce military reliance on conventional fossil fuels and reconfigure its energy sourcing, thus reducing dependence on imported hydrocarbons; this is with an eye towards ultimately severing the logistical relationship between existing energy infrastructures and the spaces of military intervention. Taking an integrated lens of political ecology and geopolitics - 'geopolitical ecology' - we seek to provide an understanding of the production of weaponized nature. We demonstrate that the US military's discursive use of climate change to justify the provision of new military hardware and advanced biofuels promotes a vision of resource conflicts to support the development of technologies to overcome the constraints to delivery of fuel to emergent front lines. We argue that while this may appear to be militarized greenwashing, it signals a shift in the logics and practices of fuel sourcing driven by a dystopian vision of climate change, which the US military played a significant role in creating. Highlights: The US Navy is integral in the development of a domestic biofuels industry. This support is part of the Navy's overarching climate change strategy. The ultimate end is to reconfigure Navy operations. Political ecology can benefit from incorporating geopolitical perspectives.